SOBRATAFE GLOBAL ADVANCED WOUND CARE MEETING 2021 - Tratamento, SOBRATAFE Sociedade Brasileira de (Revista Enfermagem Atual In Derme, 2021)
Winners of the "DR. Walter Soares Pinto" E-poster award at the SGAWCM 2021 – SOBRATAFE Global Advanced Wound Care Meeting 2021